The Influence of Brand Image and Product Placement on Scarlett's Product Purchase Decision in Korea Today's Webtoon Drama through Purchase Interest as an Intervening Variable - Fitri Fadhila; Nur Hajati; Ridwan Basalamah (Budapest International Research and Critics University, 2023)
This study aims to analyze the role of buying interest in mediating brand image and product placement on purchasing decisions. The sample of this research is Scarlett Whitening users who are in Malang City with the criteria of having watched the Korean drama Today's Webtoon. The sample in this study used a purposive sampling technique totaling 80 respondents. The data analysis method is descriptive quantitative. Quantitative analysis was performed using SmartPLS. In this study get the result that. Brand image has a significant effect on purchase intention, product placement has a significant effect on purchase intention, brand image has a significant effect on purchase decisions, product placement has no significant effect on purchase decisions, purchase intention has a significant effect on purchase decisions, brand image has a significant effect on purchase decisions through interest purchase, product placement has no significant effect on purchasing decisions through buying interest